Banks' performance and economic growth in India: A panel cointegration analysis - Md Shabbir Alam; Mustafa Raza Rabbani; Mohammad Rumzi Tausif; Joji Abey (Economies, 2021)
The banking sector plays a crucial role in the economic growth of a nation. The purpose of this study is to examine the long-term association between banks' performance and the economic growth of a developing economy: India. The study used a panel of data of 20 public sector banks for the period 2009 to 2019. It applied the Pedroni and Kao test of co-integration, panel vector error correction model (VECM) dynamic, panel fully-modified ordinary least squires OLS (FMOLS), and dynamic OLS (DOLS) to estimate the relationship of interest margin return on assets, bank investment, and lending capacity of the bank with gross domestic product (GDP) of the country. The identification and incorporation of these bank-related variables are the innovations of this study. The results indicate that the bank-related variables are co-integrated with economic growth. Further analysis indicates a significant relationship between interest margin and return on assets with economic growth. In addition, lending capacity and investment activities are not significantly associated with economic growth, leading to the policy recommendation to improve upon these two factors in order to achieve higher growth rates.
Keywords: 330; bank performance; economic growth; return on assets; bank investment; panel cointegration; India